Consider the following three-step representation of a reaction mechanism. Step 1: A + B mc016-1.jpg AB (fast) and the rate = k[A][B] Step 2: AB + B mc016-2.jpg AB2 (slow) and the rate = k[AB][B] Step

[ad_1]

Consider the forthcoming three-trudge resemblance of a reaction mechanism. Trudge 1: A + B mc016-1.jpg AB (fast) and the admonish = k[A][B] Trudge 2: AB + B mc016-2.jpg AB2 (slow) and the admonish = k[AB][B] Trudge 3: AB2 + B mc016-3.jpg AB3 (fast) and the admonish = k[AB2][B] Overall: A + 3B mc016-4.jpg AB3 and the admonish = k[A][B]2 Which explains why the admonish law for the overall equation is not the corresponding as the admonish equation for the admonish-determining trudge?

Show further

[ad_2]
Source integrate